Borneol, a messenger agent, improves central nervous system drug delivery through enhancing blood-brain barrier permeability: a preclinical systematic review and meta-analysis - Qun Zheng; Zi-Xian Chen; Meng-Bei Xu; Xiao-Li Zhou; Yue-Yue Huang; Guo-Qing Zheng; Yan Wang (Taylor & Francis Group, 2018)
To achieve sufficient blood-brain barrier (BBB), penetration is one of the biggest challenges in the development of diagnostic and therapeutic for central nervous system (CNS) disorders. Here, we conducted a systematic review and meta-analysis to assess the preclinical evidence and possible mechanisms of borneol for improving co-administration of CNS drug delivery in animal models. The electronic literature search was conducted in six databases. Fifty-eight studies with 63 comparisons involved 1137 animals were included. Among 47 studies reporting the assessments of CNS drug concentration, 45 studies showed the significant effects of borneol for improving CNS drug delivery (p<.05), whereas 2 studies showed no difference (p>.05). Nineteen comparisons showed borneol up-regulated BBB permeability (p<.05) using brain EB content (n = 8), Rh 123 content (n = 4), brain imaging agent content (n = 2), brain water content (n = 1) and observing ultrastructure of BBB (n = 4), whereas three studies showed no difference or unclear results. Seven studies reported the safety, in which one study showed borneol was reversible changes in the BBB penetration; six studies showed borneol did not increase co-administration of blood drugs concentration of peripheral tissues (p > .05). Effects of borneol are closely associated with inhibition of efflux protein function, releasement of tight junction protein, increasement of vasodilatory neurotransmitters, and inhibition of active transport by ion channels. In conclusion, borneol is a promising candidate for CNS drug delivery, mainly through mediating a multi-targeted BBB permeability.